ANALISIS FAKTOR YANG MEMPENGARUHI HUMAN DEVELOPMENT INDEX (HDI) PADA 6 DAERAH TERTINGGAL DI PULAU JAWA TAHUN 2010-2016 - Yunita Firdha Kyswantoro (Jurnal Ekonomi Pembangunan, 2017)
Disadvantaged areas are districts whose areas and communities are less developed when compared to other regions on a national scale. Java Island as the contribution of the highest economic growth in Indonesia in fact accounted for 6 of 122 disadvantaged areas in Indonesia, namely Kab. Bondowoso, Kab. Situbondo, Kab. Bangkalan, Kab.Sampang, Kab. Pandeglang, Kab. Lebak. One of the criteria of disadvantaged areas is human resources, this can be measured through HDI (Human Development Index). The number of poor people, labor force and GRDP per capita are some factors that are considered to illustrate the influence of HDI in 6 disadvantaged areas. This research used Random Effect Model (REM) panel data regression in 6 disadvantaged areas in Java Island 2010 - 2016. The result of this research, labor force variable has no significant effect to Human Development Index (HDI). While the number of poor and PDRB perkapita have a significant effect on HDI in 6 disadvantaged areas in Java. It is therefore an effective way to accelerate the growth of economic growth in underdeveloped areas related to HDI through the decline of the number of poor people with the creation of labor-intensive jobs which in turn will increase the per capita GDP. Thus, increasing GRDP per capita will increase Human Development Index (HDI) where HDI is one indicator in economic growth of a region.